The Equation of Iconography of Cracking Bodies in Bapsi Sidhwa's Cracking India - GC, Saroj (Literary Studies, 2020)
Lenny, a young Parsi girl coming of age at the time of Partition and independence, in Sidhwa’s novel Cracking India, says “there is no space for us in Queen’s Garden”. She basically refers to the literal space— the lack of space to accommodate herself and other friends in the Garden, for it is being crowded because of increasing communal violence. However, Lenny’s literality of questioning the space cannot be taken for granted. This voice of the innocent, Lenny triggers prominent thematic content in social-cultural context of Partition. If her search for space is seen in broad spectrum of Partition violence of 1947 in India, she as representative of both female figures and the neutral and the marginalized people, is seeking more significant space in context of Partition violence; it is a search for the space for female in nationalist discourse. The search, by the same token, corresponds with the objective and the rhetoric of Sidhwa— questioning the historiography of nationalist discourse. Looking from this perspective, space is not just literal one. Additionally, the “Queen’s Garden” becomes metonymic manifestation of the project of empire, or cultural mission of colonization, and the subsequent consequence, nationalism.